2005
DOI: 10.4269/ajtmh.2005.72.702
|View full text |Cite
|
Sign up to set email alerts
|

Coinfection With Plasmodium Falciparum and Schistosoma Haematobium: Protective Effect of Schistosomiasis on Malaria in Senegalese Children?

Abstract: Studies with animal models have suggested the possibility of interactions between parasites during concurrent infections and have raised the question of a similar phenomenon in humans. The present survey was undertaken to assess the impact of urinary schistosomiasis on the susceptibility of children to malaria. It was carried out in Senegal between September 2001 and March 2002 among 523 children 3-15 years of age. We tested the association between Plasmodium falciparum densities and the load of Schistosoma ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
130
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 131 publications
(147 citation statements)
references
References 25 publications
14
130
3
Order By: Relevance
“…7 The present long follow-up study aims to confirm the protective effect of S. haematobium on P. falciparum infection found in the previous work thus establishing in a more stable way the infectious status of the individuals with both parasites.…”
Section: Introductionmentioning
confidence: 51%
See 1 more Smart Citation
“…7 The present long follow-up study aims to confirm the protective effect of S. haematobium on P. falciparum infection found in the previous work thus establishing in a more stable way the infectious status of the individuals with both parasites.…”
Section: Introductionmentioning
confidence: 51%
“…5,6 A study of coinfection between malaria and schistosomiasis in humans, conducted in 2002 among children in Senegal, has concluded on the existence of a negative association between Plasmodium falciparum parasite densities and Schistosoma haematobium infection. 7 Another study among children in Mali in [2002][2003] with both an epidemiological and a biological approach, showed an age-dependent protection in children infected with urinary schistosomiasis against acute P. falciparum malaria. 8,9 However, other studies suggested an additive or synergic effect of coinfection, 10,11 as for example, Wilson and others 11 who showed that concurrent chronic exposure to Schistosoma mansoni and P. falciparum could have a synergistic effect on childhood morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The Bulinus snails, resulting in a high level of both Plasmodium falciparum malaria and of urinary schistosomosis in the community (Briand et al, 2005). 518 children, aged between 15 and 74 months old at the start of the study, were eligible.…”
Section: Study Area and Populationmentioning
confidence: 99%
“…31 The increasing interest on the co-infection relationship of Plasmodium + intestinal parasites arose partly because of the hypothesis that Th2 polarized immune response elicited by intestinal helminthes could alter the natural immune response of the host to Plasmodium parasites. 32,33 A study by Spiegel et al 34 indicate that parasitic infections have a negative effect on host response to malaria, including increased susceptibility to Plasmodium infection and increased severity of disease, while Briand et al 35 argued that it generate a protective effect, such as decreased risk of cerebral malaria and lower incidence of malaria. Yet still, Bejo et al 36 think that co-infection of Plasmodium+intestinal parasites does not have any effect on the susceptibility to malaria or in the pathologic effect of Plasmodium infections.…”
mentioning
confidence: 99%